Influence of Lorentz Invariation Violation on Arbitrary Spin Fermion Tunneling Radiation in the Vaidya-Bonner Space-Time. (18th March 2020) - Zhang, Jie; Liu, Zhie; Sha, Bei; Tan, Xia; Liu, Yuzhen; Yang, Shuzheng
Abstract : In the space-time of the nonstationary spherical symmetry Vaidya-Bonner black hole, an accurate modification of Hawking tunneling radiation for fermions with arbitrary spin is researched. Considering a light dispersion relationship derived from string theory, quantum gravitational theory, and the Rarita-Schwinger equation in the nonstationary spherical symmetry space-time, we derive an accurately modified dynamic equation for fermions with arbitrary spin. By solving the equation, the modified tunneling rate of fermions with arbitrary spin, Hawking temperature, and entropy at the event horizon of the Vaidya-Bonner black hole are presented. We find that the Hawking temperature will increase, but the entropy will decrease compared with the case without the Lorentz Invariation Violation modification.